Isolation of Lytic Bacteriophages infected Indonesian-strain Vibrio parahaemolyticus and its Protective Effects on Brine Shrimp (Artemia sp.) - Dinamella Wahjuningrum; Putri Shandra Ramhirez; Laely Nuzullia; Munti Yuhana; Sukenda Sukenda; Hasan Nasrullah (Jurnal Ilmiah Perikanan dan Kelautan)
Graphical Abstract